Karakteristik Fisiko-Kimia dan Sensori Nugget Rumput Laut dengan Penambahan Tepung Ikan Motan (Thynnichthys thynnoides) - Ricky Setyo Aditomo; Rodiana Nopianti; Indah Widiastuti (Universitas Sriwijaya, 2017)
The purpose of the research was to know the physicochemical and sensory characteristic of seaweed nugget with an addition of carp fish meal. The research was conducted from March 2016 until February 2017. The research method used a randomized block design (RBD). The treatments were 0%, 10%, 20%, 30% and 40% of fish meal. The parameters of this research were chemical analysis such as water content, ash content, protein content, carbohydrate content, and calcium; physical analysis was hardness, color and sensory analysis (color, taste, and texture). The results showed that treatments gave significant effect on water content, ash content, protein content, lipid content, carbohydrate content, calcium, lightness, chroma, hardness, and taste, but there was no effect on hue, color and texture. The water content was 47.01%-48.19%, ash was 1.29%-4.36%, protein was 2.26%-7.10%, lipid was 11.83%-14.79%, carbohydrate was 26.75%-36.42%, calcium was 15.11 mg/100g-48.46 mg/100g. The lightness of this seaweed nugget were 33.70%-63.43%, chroma 25.00%-35.10%, texture 26.97 gf – 50.80 gf. Taste sensory analysis of seaweed nugget were 2.72 (unlike) – 3.84 (like). The best treatment found in this research was A1.